2022
DOI: 10.1021/acs.jpcc.2c01044
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Indirect Gap and the Direct Optical Transitions at the High-Symmetry Point of the Brillouin Zone and Band Nesting in MoS2, MoSe2, MoTe2, WS2, and WSe2 Crystals

Abstract: Following the rise of interest in the properties of transition metal dichalcogenides, many experimental techniques were employed to research them. However, the temperature dependencies of optical transitions, especially those related to band nesting, were not analyzed in detail for many of them. Here, we present successful studies utilizing the photoreflectance method, which, due to its derivative and absorption-like character, allows investigating direct optical transitions at the high-symmetry point of the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…In order to determine the energy of the absorption edge and its nature, both the square root and square of the absorption spectrum, which corresponds to the indirect and direct absorption edge, respectively, were plotted and analyzed. 29…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine the energy of the absorption edge and its nature, both the square root and square of the absorption spectrum, which corresponds to the indirect and direct absorption edge, respectively, were plotted and analyzed. 29…”
Section: Resultsmentioning
confidence: 99%
“…In order to determine the energy of the absorption edge and its nature, both the square root and square of the absorption spectrum, which corresponds to the indirect and direct absorption edge, respectively, were plotted and analyzed. 29 An exemplary analysis is shown in Fig. S8 in the ESI † and shows that with an increase in energy, there is first an indirect interband absorption and then a direct interband absorption which is much stronger.…”
Section: Journal Of Materials Chemistry C Papermentioning
confidence: 99%
“…Experimentally, bismuthene's fundamental optical excitation spectrum is probed via highly spatially-resolved photomodulated reflectivity (PR). PR is a very sensitive probe that has been successfully applied to study the excitonic spectrum of atomically thin crystals 41,42 , since it directly probes the derivative of the absorption spectrum with respect to energy, in stark contrast to direct reflectivity techniques.…”
Section: Results Ii: Optical Spectroscopy Optical Gap and Excitonic R...mentioning
confidence: 99%
“…Further proof of the resonant origin of our S-modes could be provided with temperature dependent measurements. Indeed, it was recently shown that the indirect band gap of bulk MoSe 2 increases of about 100 meV by lowering the temperature [52]. We thus aim at further demonstrate the resonant origin of the S modes by driving the sample out of resonance with external temperature.…”
Section: B Temperature Dependence Of Raman Peaksmentioning
confidence: 94%